Irrigação localizada na cultura do feijoeiro na depressão central - RS - Rodrigues, Cleber Millani (2009)
During the second harvest in the central region of Rio Grande do Sul, pluvial precipitations are usually irregularly distributed along the bean production cycle. This irregular distribution of rains during the bean cultivation can affect its productive potential. Complementary irrigation can be adopted in order to avoid drought stress. In current agriculture, irrigation systems have been increasingly used to supply crops and promote better conditions for cultivation, prompting an increase in productivity. The localized irrigation is one of these systems which are usually applied in perennial cultures and/or small areas. It has been used as a resource for diminishing energy consumption and for prompting more efficacy in water consumption. The bean culture has a high market price and is very susceptible to drought stress. These factors contribute for its cultivation in fields with the use of irrigation systems. Besides endeavoring to offer better parameters for irrigators, this work aims at determining the necessity of complementary irrigation and verifying the relation between localized irrigation systems and water availability by means of different critical water levels applied in complementary irrigation in bean crops. The variety used was the BRS Valente, seeded outof- season in Santa Maria, central region of Rio Grande do Sul, Brazil. The micro-sprinkling and subsurface dripping irrigation systems were used to sustain the highest complementary irrigation depths in 20, 40 and 60 mm of maximum evapotranspiration accumulated and a control treatment without irrigation. The reference vapotranspiration was measured by means of a meteorological station installed at UFSM and its estimative was calculated by the Penman-Monteith equation. There were differences between the treatments in the complementary irrigation levels regarding some production factors and the different systems of irrigation (micro-sprinkling and subsurface dripping irrigation systems).